Association of the consumption of common drinks with early puberty in both sexes - Tsai, Meng-Che; Lee, Yungling Leo; Chen, Yang Ching (Frontiers in Public Health, 2022)
Background: We examined the effect of sugar-sweetened beverages (SSB) and common drink intake on pubertal development in both sexes. Methods: Data were retrieved from Taiwan Children Health Study, which involved detailed pubertal stage assessments of 2819 schoolchildren aged 11 years in 2011–2012. Drawings of secondary sexual characteristics and self-reported age at menarche or voice breaking were used to assess pubertal stages. Dietary intake was assessed using a detailed semi-quantitative food frequency questionnaire. Generalized estimating equation modeling was applied to obtain odds ratios (ORs) and 95% confidence intervals (CIs) to represent the effects of each drink on early pubertal development outcomes. Results: In boys, an one cup/day increment of a SSB was associated with earlier voice breaking (β= −0.12; 95% CI = −0.20, −0.04), whereas consuming yogurt (≥2 cups/day) was a protective factor against early puberty (OR = 0.78; 95% CI = 0.73, 0.83). In girls, SSB consumption was associated with increased risk of early puberty in a dose–response manner, and a similar protective effect of yogurt consumption and fermented probiotic drink (≥2 cups/day) against early puberty was observed (OR = 0.96; 95% CI = 0.94, 0.99). Furthermore, the intake of both total sugar and added sugar within SSBs increased risk of early puberty in girls but not in boys. Conclusions: SSBs were associated with early puberty, and probiotic drinks appeared to mitigate this link. These findings indicate that the gut–brain axis could play a crucial role in sexual maturation.